The journal of a voyage to Lisbon. - Fielding, Henry, 1707-1754 (Floating Press, 2010)
Best known for his novels Tom Jones and Amelia, Henry Fielding was also an intrepid traveler and explorer who used his journeys around the world as fodder for his sprawling, picaresque works of fiction. Journal of a Voyage to Lisbon, Volume I collects Fielding's impressions of his trip to Portugal's capital. A must-read for fans of lively travel writing.